2021
DOI: 10.1017/s0007114521000416
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalisations for falls and hip fractures attributable to vitamin D deficiency in older Australians

Abstract: Vitamin D deficiency is associated with increased risk of falls and fractures. Assuming this association is causal, we aimed to identify the number and proportion of hospitalisations for falls and hip fractures attributable to vitamin D deficiency [25 hydroxy D (25(OH)D) <50 nmol/L] in Australians aged 65 years and over. We used 25(OH)D data from the 2011/12 Australian Health Survey and relative risks from published meta-analyses to calculate population attributable fractions for falls and hip fracture. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…The study of Lauretani et al conducted on 974 Italian patients with an average age of 85.7 admitted to hospital because of HFs showed that 84.2% of them had a vitamin D3 deficiency [ 70 ]. Similar relationships were presented by Johnson et al [ 71 ] and Neale et al [ 72 ], who conducted studies among patients who live in sunny areas.…”
Section: Hip Fracturessupporting
confidence: 83%
See 1 more Smart Citation
“…The study of Lauretani et al conducted on 974 Italian patients with an average age of 85.7 admitted to hospital because of HFs showed that 84.2% of them had a vitamin D3 deficiency [ 70 ]. Similar relationships were presented by Johnson et al [ 71 ] and Neale et al [ 72 ], who conducted studies among patients who live in sunny areas.…”
Section: Hip Fracturessupporting
confidence: 83%
“…Consequently, decreased serum vitamin D levels seem to be associated with an increased risk of falls and hip fractures. The above analyzed studies also implied that the problem of deficiency applies to very sunny countries [ 71 , 72 ], which suggests the implementation of preventive supplementation with vitamin D3 in the general population, regardless of the place of residence. Studies have also shown the validity of vitamin D3 supplementation after HF as a potential factor improving recuperation [ 66 , 76 , 77 ].…”
Section: Hip Fracturesmentioning
confidence: 99%
“…However, as per Rizzoli et al, 11 recommended general measures to counter fragility fractures include insuring the presence of vitamin D sufficiency. This idea appears reasonable given that as per Neale et al, 12 even in a sunny country like Australia sufficient numbers of falls and hip fractures are attributable to a vitamin D deficiency in the affected older adults. Current research further reveals that vitamin D combined with calcium reduces the risk of hip fracture although on its own may not exhibit tangible effects but this could reflect the nature of available studies.…”
Section: Specific Observationsmentioning
confidence: 89%
“…Figure 1 Points at which vitamin D or a lack thereof may influence the hip fracture risk cycle [Key reference sources: 3,6,11,12,16,17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D deficiency as defined at this concentration is associated with increased risk of hip fractures in people aged 60 years and over [ 257 ]. It has been estimated that, assuming this association is causal, approximately 8% of hip fractures occurring in adults aged ≥ 65 years in Australia are attributable to vitamin D deficiency (25(OH)D < 50 nmol L −1 ) [ 258 ]. Falls in older adults have also been linked to 25(OH)D concentration < 50 nmol L −1 [ 259 ].…”
Section: Benefits Of Exposure To Uv Radiationmentioning
confidence: 99%